Evaluation of Analgesic Drug Therapy for Postoperative Pain Management in Cardiovascular Surgery - Yue Yue, MBBS; Hongyan Ji, MBBS; Shizhong Wang, PhD; Huawei Cheng, MBBS; Rongmei Wang, MSc; Haijun Qu, MSc; Jing Li, MSc (Elsevier, 2024)
ABSTRACT: Background: Cardiovascular surgery is usually associated with higher degree of postoperative pain that influences a patient's physical recovery. Multiple clinical measures have been taken to avoid overuse of opioid agents for postoperative pain management, which led to the development of clinical pathways for analgesic drug treatment using a multimodal approach. Objective: To evaluate the effectiveness and safety of a multimodal postoperative analgesic drug pathway (ADP) for pain management following cardiovascular surgery. Methods: This retrospective, controlled, nonrandomized study evaluated a postoperative ADP in patients undergoing cardiovascular surgery in a tertiary general hospital in Qingdao, China. Effectiveness and safety outcomes were compared before and after the implementation of the ADP. Outcome indicators included postoperative pain scores, consumption of opioids in analgesic pumps, and incidence of adverse events. Results: Patients who underwent cardiovascular surgery from September to November 2021 before the implementation of the ADP (n = 193) and from September to November 2022 after the implementation of the ADP (n = 218) were enrolled. Pain scores were reduced on day 1, 3, and 5 after surgery and the reduction was most significant in mild pain (P < .001). Opioids in analgesic pumps consumption was also significantly reduced and there was decreased incidence of adverse events such as nausea and vomiting (P = .026), respiratory inhibition (P = .027), and dizziness and headache (P = .028) in cardiovascular surgery patients after implementation of the ADP. Conclusions: Improved effectiveness and safety were observed following the implementation of the ADP. Multimodal analgesic ADP methodology can be effectively used for postoperative pain management in patients undergoing cardiovascular surgery.